2021
DOI: 10.1021/acsenergylett.1c01513
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Mass Transport Regimes in Gas Diffusion Electrodes for CO2 Electroreduction

Abstract: Gas diffusion electrodes (GDEs) have shown promising performance for the electrochemical reduction of CO2 (CO2R). In this study, a resolved, pore scale model of electrochemical reduction of CO2 within a liquid-filled catalyst layer is developed. Three CO2 mass transport regimes are identified in which the CO2 penetration depth is controlled by CO2 consumption in the electrolyte, CO2 conversion along the solid-electrolyte double-phase boundaries (DPBs), and CO2 conversion concentrated around the gas–solid–elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Accordingly, the rate of the homogeneous reaction is only a function of CO 2 and hydroxide concentrations as follows, This framework for modeling the (bi)­carbonate equilibrium is far simpler than accounting for all (bi)­carbonate equilibrium reactions (which are shown in the first five rows of Table ). Moore et al used this simplifying assumption in a resolved pore model to predict mass-transfer and kinetic control regimes for aqueous CO 2 reduction in highly alkaline electrolyte . By neglecting the reversibility of the (bi)­carbonate equilibrium, the authors showed that the consumption of CO 2 by homogeneous reactions, surface reactions, and reactions at a triple phase can be compared using a simple reaction diffusion equation.…”
Section: General Aspects and Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the rate of the homogeneous reaction is only a function of CO 2 and hydroxide concentrations as follows, This framework for modeling the (bi)­carbonate equilibrium is far simpler than accounting for all (bi)­carbonate equilibrium reactions (which are shown in the first five rows of Table ). Moore et al used this simplifying assumption in a resolved pore model to predict mass-transfer and kinetic control regimes for aqueous CO 2 reduction in highly alkaline electrolyte . By neglecting the reversibility of the (bi)­carbonate equilibrium, the authors showed that the consumption of CO 2 by homogeneous reactions, surface reactions, and reactions at a triple phase can be compared using a simple reaction diffusion equation.…”
Section: General Aspects and Equationsmentioning
confidence: 99%
“…Phase diagram for mass-transport regimes as a function of pore radius and CO evolution current density ( i COER ) for a pore pH (pH pore ) of (f) 14 and (g) 13. Adapted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Survey Of Macroscale Models Employed For Modeling Porous Ele...mentioning
confidence: 99%
“…At low flow rates the electrolyte floods the entire GDE, resulting in mass transport limitations and increased HER. It is unlikely that this flooding is occurring in the catalyst layer alone, as previous literature has demonstrated that the CO 2 diffusion layer thickness is on the order of microns rather than nanometers. We present in Figure the three idealized states in which a catalyst layer can exist. In reality it is likely that the true wetting of the catalyst layer occurs as a combination of all three idealized states.…”
mentioning
confidence: 99%
“…Electrolyte and mass transfer of reaction intermediates are crucial parameters for electrocatalytic reactions, as CO 2 reduction, , hydrogen evolution, ,, and oxygen evolution, because concentration profiles at the interface might severely depart from the bulk electrolyte composition. ,, For instance, alkaline pH at the surface is expected to promote CO 2 reduction to C 2+ to the detriment of C 1 products. Laser-microstructured cavities on copper allowed the local tuning of surface pH and CO 2 concentrations, confirming high Faradaic Efficiency (FE) toward ethanol, ethylene, and propanol for alkaline pH and intermediate CO 2 concentration . Further investigations with pulsed CO 2 reduction proved a 2-fold effect of anodic bias in lowering the surface pH and stabilizing and/or generating polarized sites .…”
Section: Challenges From Electrocatalytic Processes Under Working Con...mentioning
confidence: 95%